Induced mutation and epigenetics modification in plants for crop improvement by targeting CRISPR/Cas9 technology. Issue 6 (4th January 2018) - Khan, Muhammad Hafeez Ullah; Khan, Shahid U.; Muhammad, Ali; Hu, Limin; Yang, Yang; Fan, Chuchuan
Abstract : Clustered regularly interspaced palindromic repeats associated protein Cas9 (CRISPR‐Cas9), originally an adaptive immunity system of prokaryotes, is revolutionizing genome editing technologies with minimal off‐targets in the present era. The CRISPR/Cas9 is now highly emergent, advanced, and highly specific tool for genome engineering. The technology is widely used to animal and plant genomes to achieve desirable results. The present review will encompass how CRISPR‐Cas9 is revealing its beneficial role in characterizing plant genetic functions, genomic rearrangement, how it advances the site‐specific mutagenesis, and epigenetics modification in plants to improve the yield of field crops with minimal side‐effects. The possible pitfalls of using and designing CRISPR‐Cas9 for plant genome editing are also discussed for its more appropriate applications in plant biology. Therefore, CRISPR/Cas9 system has multiple benefits that mostly scientists select for genome editing in several biological systems. Abstract : The present review will encompass how CRISPR‐Cas9 is revealing its beneficial role in characterizing plant genetic functions, genomic rearrangement, how it advances the site‐specific mutagenesis, and epigenetics modification in plants to improve the yield of field crops with minimal side‐effects.